2011
DOI: 10.1080/19424280.2011.575832
|View full text |Cite
|
Sign up to set email alerts
|

Footwear traction and lower extremity non-contact injury

Abstract: For the past forty years footwear traction has been thought to be one of the causes of noncontact lower extremity injury in sport. Previous studies have shown that rotational traction was associated with ACL injury, however, no studies have determined the relationship between footwear traction, both translational and rotational, and all lower extremity non-contact injuries. Therefore, the purposes of this thesis were to 1) determine if a relationship exists between an athlete's specific footwear traction (both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Increases in translational traction do increase joint loading for certain movements, which could lead to an increase in injury risk. However, the injury study showed that after a certain value, further increases in translational traction were associated with a drop off in the injury rate (Wannop et al, 2013). The results of the current study cannot explain the drop in injury rate with increasing translational traction, but the results do provide support to the fact that translational traction can influence joint loading and potentially joint injury.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Increases in translational traction do increase joint loading for certain movements, which could lead to an increase in injury risk. However, the injury study showed that after a certain value, further increases in translational traction were associated with a drop off in the injury rate (Wannop et al, 2013). The results of the current study cannot explain the drop in injury rate with increasing translational traction, but the results do provide support to the fact that translational traction can influence joint loading and potentially joint injury.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, these studies did not speculate why or how rotational traction may affect injuries. The results from Wannop et al (2013) indicate that not only rotational traction but also translational traction can have an effect on lower extremity non-contact injuries. This study revealed that the individual components of both rotational traction as well as translational traction can influence joint loading, indicating that both components are important when related to injury risk.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations